2016
DOI: 10.1016/j.asd.2016.10.006
|View full text |Cite
|
Sign up to set email alerts
|

Immunolocalization of cuticular proteins in Johnston's organ and the corneal lens of Anopheles gambiae

Abstract: Previous work with EM immunolocalization examined the intracuticular placement of several antibodies directed against cuticular proteins (CPs) in various structures of Anopheles gambiae. Those structures had long stretches of fairly uniform cuticle. We have now used 19 antibodies directed against members of five CP families on two adult structures with considerable complexity, Johnston's organ and the corneal lens of the compound eye. We also localized chitin with colloidal-gold labeled wheat germ agglutinin. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Fluorescence in situ hybridization would allow overexpressed proteins from cuticle genes to be localised to make sure they belonged to at least one of three cuticle layers. None of the cuticular proteins necessarily belongs to the cuticle since some of them have been found in Johnston’s organ and the corneal lens of Anopheles gambiae using EM immunolocalization 62 . In addition, some cuticle proteins with chitin-binding domain 2 belong to the procuticle and also to the midgut chitinous peritrophic matrix in Drosophila melanogaster 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Fluorescence in situ hybridization would allow overexpressed proteins from cuticle genes to be localised to make sure they belonged to at least one of three cuticle layers. None of the cuticular proteins necessarily belongs to the cuticle since some of them have been found in Johnston’s organ and the corneal lens of Anopheles gambiae using EM immunolocalization 62 . In addition, some cuticle proteins with chitin-binding domain 2 belong to the procuticle and also to the midgut chitinous peritrophic matrix in Drosophila melanogaster 63 .…”
Section: Discussionmentioning
confidence: 99%
“…Sclerotisation of the cuticle is a primary consequence of the formation of cross-links between cuticle proteins, resulting in a rigid matrix in which chitin microfibrils can be embedded. Additionally, it has been demonstrated that cuticular proteins with low-complexity sequences play an integral role as cross-linked structural proteins in the formation of lightweight rigid cuticles [ 46 ]. The CPLCG family was first identified in A. gambiae by proteomic analysis of cuticle preparations, and members of the CPLCG family contain low-complexity regions (LCRs) [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Those eliminated are shown with brackets around the U or S in the green colored cells on Table 1, leaving only 14 as larval-restricted. Furthermore, our EM immunolocalization studies revealed that antibodies raised against CPR22, CPR61, and CPR133/CPR153 reacted with proteins in adult structures (Vannini and Willis, 2016, 2017), revealing that they are not restricted to larvae, although this information was not used in our numerical summaries. We failed to detect any CPs that might be restricted to pupae.…”
Section: Resultsmentioning
confidence: 98%
“…One protein, CPR152, does appear to be unique in that by in situ hybridization it was restricted to Johnston’s organ and EM immunolocalization revealed it to be localized in several, but not all, discrete components of that structure (Vannini and Willis, 2016). We also recovered peptides for CPR152 from the rest of the antennae but nowhere else.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation